2021
DOI: 10.7150/ijms.51064
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mutation Burden, Immune Cell Infiltration, and Construction of Immune-Related Genes Prognostic Model in Head and Neck Cancer

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common malignancy worldwide, and the prognosis of HNSCC remains bleak. Numerous studies revealed that the tumor mutation burden (TMB) could predict the survival outcomes of a variety of tumors. Objectives: This study aimed to investigate the TMB and immune cell infiltration in these patients and construct an immune-related genes (IRGs) prognostic model. Methods: The expression data of 546 HNSCC patients were obtained from The Cancer Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 50 publications
8
30
0
Order By: Relevance
“…Patients with bladder cancer with higher TMB levels have a better prognosis ( Fan et al, 2020 ; Mi et al, 2020 ; Wu et al, 2020 ). However, in head and neck squamous cell carcinoma and melanoma, high TMB can lead to a shorter survival period, which may be related to infiltrating immune cells ( Jiang et al, 2020 , 2021 ). The above results indicate that the cellular components of the tumor involved in the immune response are complex, which leads to different immunotherapy effects in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with bladder cancer with higher TMB levels have a better prognosis ( Fan et al, 2020 ; Mi et al, 2020 ; Wu et al, 2020 ). However, in head and neck squamous cell carcinoma and melanoma, high TMB can lead to a shorter survival period, which may be related to infiltrating immune cells ( Jiang et al, 2020 , 2021 ). The above results indicate that the cellular components of the tumor involved in the immune response are complex, which leads to different immunotherapy effects in patients.…”
Section: Discussionmentioning
confidence: 99%
“…We considered this to be MSI high in the high-risk group and MSI low in the low-risk group, due to the tumor’s disrupted function during DNA damage repair leading to increased gene instability, which is consistent with the results of TMB in the high and low risk groups. Jiang et al (2021) found that patients with high TMB had worse survival outcomes than those with low TMB. We believe that this finding may account for the longer DFS in the low-risk group, compared to the high-risk group.…”
Section: Discussionmentioning
confidence: 97%
“…42 TMB and MSI have been considered new biomarkers of immunotherapy response and potential predictors of response to immune checkpoint inhibitors (ICIs). 43,44 The TMB score analysis revealed that the expression level of six survival-related mutated genes was significantly positively correlated with TMB in…”
Section: Discussionmentioning
confidence: 99%